Pengembangan Content Management System pada Admisi Online Binus University - Iskandar, Karto; Jefriyanto, Jefriyanto; Giovanni, Halena; Gunawan, Candra (ComTech: Computer, Mathematics and Engineering Applications, 2012)
Technically registration form for new Binus institution must be regenerated and not dynamic. Therefore, this research is objected to simplify the creation of registration process for new Binus institution and provide solutions to the problem when Binus establish other new institutions. Methodology used is analysis and design of the database (database oriented). Analysis is done by asking the problems of existing systems in the IT Directorate, whereas the design uses UML diagram notation 2.0. The results obtained is front end and back end applications for the Content Management System of the registration form. The results of this design can be used to simplify the new student registration or in the many Binus institutions by grouping similar fields. With some changes in the front end and back end applications for content Management System, the addition of new online admission application form can be managed faster, where the creation of admision registration form is managed in the back end application. As suggestions for future development, online admission registration can be run in mobile version.